FeS2@N-C nanorattles encapsulated in N/S dual-doped graphene/carbon nanotube network composites for high performance and high rate capability anodes of sodium-ion batteries - KANDULA, SYAM; Youn, Beom Sik; Cho, Jinhan; Lim, Hyung-Kyu; Son, Jeong Gon (Elsevier BV, 2022)
Developing effective anode materials for sodium-ion batteries (SIBs) remains challenging. Although FeS2 has a high theoretical capacity, it suffers from significant volume changes during charge/discharge and forms soluble polysulfides at lower potentials (below 0.8 V vs. Na/Na+), making practical application difficult. We have developed an effective strategy to synthesize N-doped carbon-coated FeS2 nanorattles encapsulated in N/S dual-doped graphene/single-walled carbon nanotubes (G/SWCNTs) via hydrothermal vulcanization (FSCGS). This approach enabled the simultaneous formation of nanorattle structures and N/S dual-element doping into the G/SWCNT network. Using the FSCGS sample as an anode for SIBs, a remarkable specific capacity of 1,190 mAh g？1 at a current density of 0.1 A g？1 was achieved, with an excellent rate capability of 476 mAh g？1 at 10.0 A g？1. Moreover, it exhibited superior cyclic stability, with a capacity retention of 91.3% at 0.5 A g？1 after 200 cycles. First-principles calculations revealed that pyridinic-N/S doping of the basal graphene network improved Na+ reduction, resulting in enhanced electrochemical performance. The effective electrochemical functioning of the FSCGS anode material was attributed to an optimized hierarchical architecture and the excellent electrical conductivity/electrochemical activity provided by the dual carbon entities (N-doped carbon and N/S dual-doped G/SWCNT network). ？ 2022 The Authors